Purified Cell Wall of Saccharomyces cerevisiae Increases Protection Against Intestinal Pathogens in Broiler Chickens - Baurhoo, B.; Goldflus, F.; Zhao, X. (International Journal of Poultry Science, 2009)
A study was conducted to determine effects of a mannanoligosaccharide prebiotic, derived from cell wall of the yeast Saccharomyces cerevisiae, on morphological development of the intestines and microbial populations of the ceca and litter. Dietary treatments included: antibiotic-free diet (CTL), diet 1 + virginiamycin (VIRG; 16.5 mg/kg feed) and diet 1 + ActiveMOS (MOS; 1.5 kg/T starter diet and 1 kg/T grower diet). Each treatment was assigned to 3 pen replicates (55 birds/pen). At day 14, 24 and 34, cecal contents were used for Lactobacilli, Bifidobacteria, E. coli and Campylobacter quantification whereas litter was analyzed for Campylobacter and E. coli. At same time points, jejunum samples were used in histological analysis. MOS significantly increased goblet cell number in the jejunum (p<0.05) at day 24 and 34. In contrast to the CTL and VIRG diet, MOS consistently increased cecal populations of Bifidobacteria (p<0.05) at all times. Moreover, at day 34, MOS increased cecal populations of Lactobacilli (p<0.05) and reduced E. coli and Campylobacter concentrations (p<0.05). None of the dietary treatments altered E. coli and Campylobacter concentrations in the litter. In comparison to antibiotics, MOS, therefore, improved intestinal health conditions by increasing goblet cell number into the villi membrane, stimulating growth of beneficial bacteria and reducing colonization by pathogenic bacteria.